2019
DOI: 10.1111/1365-2656.13115
|View full text |Cite
|
Sign up to set email alerts
|

A tale of scale: Plot but not neighbourhood tree diversity increases leaf litter ant diversity

Abstract: Diversity of producers (e.g. plants) usually increases the diversity of associated organisms, but the scale (i.e. the spatial area of plant diversity considered) at which plant diversity acts on other taxa has rarely been studied. Most evidence for cross‐taxon diversity relations come from above‐ground consumers that directly interact with plants. Experimental tests of plant diversity effects on elusive organisms inhabiting the leaf litter layer, which are important for nutrient cycling and decomposition, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 69 publications
1
9
1
Order By: Relevance
“…This finding possibly indicates that the invasion‐induced leaf‐litter variation was not enough to modify the ground‐foraging ant fauna. Some previous studies have found a lack of association between the surrounding tree diversity, litter heterogeneity or depth, and the leaf‐litter ant fauna, corroborating our results (e.g., Donoso et al, 2010; Skarbek et al, 2020). These studies suggest that local‐scale factors, such as competition among ants, may be more important drivers of ant community assembly.…”
Section: Discussionsupporting
confidence: 93%
“…This finding possibly indicates that the invasion‐induced leaf‐litter variation was not enough to modify the ground‐foraging ant fauna. Some previous studies have found a lack of association between the surrounding tree diversity, litter heterogeneity or depth, and the leaf‐litter ant fauna, corroborating our results (e.g., Donoso et al, 2010; Skarbek et al, 2020). These studies suggest that local‐scale factors, such as competition among ants, may be more important drivers of ant community assembly.…”
Section: Discussionsupporting
confidence: 93%
“…when a more diverse litter layer allows for the coexistence of more ant colonies (e.g. Kaspari et al., 2000; Skarbek et al., 2020) or when a more heterogeneous vegetation structure facilitates spiders with complementary hunting strategies (e.g. Schmitz, 2009; Schuldt, Bruelheide, et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The greater plant production and increase soil cover may favour the abundance of dipterans and weeds as shelter against predators [48]. This contributes to understanding the relationships between the organisms and the sludge application similar to that of the tree density directly affecting species richness of these insects [52,53] and of ants and dung beetle species abundance and composition [22]. The vineyard canopy also correlated with ground cover after application of the sewage sludge providing greater shelter and prey availability, increasing spider survival and reproduction [48].…”
Section: Discussionmentioning
confidence: 99%